Combined Criminal Acts in the Perspective of Islamic Law and the Criminal Code - Mhd Fikri Muzaki; Abdillah Tarigan; Nikmatul Husna; Melinda Fitriana (ISNU Sumatera Utara, 2025)
Committing a Crime in the Perspective of the Criminal Code and Islamic Law aims to describe how the criminal punishment system works according to Islamic law and the Criminal Code, as well as to provide a more in-depth explanation of the combined theory of committing a crime in Islamic law and the Criminal Code. This research is a library research, which is descriptive analytical in nature. Meanwhile, in analyzing the collected data, the author uses a comparative method, namely analyzing data by comparing two different laws, namely the Criminal Code and Islamic law regarding combined punishments to find similarities and differences between the two. After the discussion, it can be concluded that: 1) there are two theories that are combined theories of committing a crime according to Islamic law, namely: first, the theory of mutual entry or al tadaahul, namely if there are several combined crimes, then several of these crimes enter into each other, second, the sharpened Absorption System, namely for combined multiple crimes where the main penalty is the same (Article 65 of the Criminal Code). Third, Cumulation System, which is a combination of multiple criminal acts against violations with violations and crimes (Article 70 of the Criminal Code), and the softened Cumulation System, which is for a combination of multiple criminal acts where the main penalty threat is not the same (Article 66 of the Criminal Code). 2) Islamic law views that the combined punishment arises as a result of the combination of committing several criminal acts where one of the acts has not yet received a final decision.